Effects of remote coaching following supervised exercise oncology rehabilitation on physical activity levels, physical fitness, and patient-reported outcomes: a randomised controlled trial - Anouk T.R. Weemaes; Milou Beelen; Matty P. Weijenberg; Sander M. J. van Kuijk; Antoine F. Lenssen (BMC, 2024)
Abstract Background Studies have shown that cancer survivors experience difficulties maintaining physical activity levels after participation in a supervised exercise rehabilitation program. This study aimed to assess the effectiveness of a six-month remote coaching intervention, following a supervised exercise oncology rehabilitation program on maintenance of PA levels; and improvement of aerobic capacity, muscle strength and patient-reported outcomes in cancer survivors. Methods Ninety-seven participants from a Dutch University Hospital's exercise rehabilitation program were randomised to the COACH group (n = 46), receiving 6 months of remote coaching after completing the exercise program, or the CONTROL group (n = 50), receiving no additional intervention. Assessment of PA levels; sedentary time; aerobic capacity; muscle strength; fatigue; health-related quality of life (HRQoL); level of anxiety and depression; and return to work (RTW) rates were conducted at baseline (T0) and six months later (T1). Multiple linear regression was used for between-group statistical comparisons of all outcomes measures. Mean differences at T1 were estimated with corresponding 95% confidence intervals (95%CI). Results No significant between-group differences were observed for all outcomes at T1. An adjusted mean difference in weekly PA of 45 min (95%CI -50;140) was observed between the COACH group and the CONTROL group, favouring the COACH group, yet lacking statistical or clinical significance. Conclusions Our six-month remote coaching intervention did not notably improve PA levels; sedentary time; aerobic capacity; muscle strength; HRQoL; fatigue; anxiety and depression symptoms and RTW rates after participation in a supervised exercise oncology program. Although the participants who received coaching showed slightly higher levels of PA, these differences were not significant. More research is needed to identify patients in need for follow-up interventions following supervised exercise program and to investigate the effectiveness of remote coaching interventions in these patients. Trial registration Dutch Trial Register NL7729, registered 13 may 2019, https://trialsearch.who.int/Trial2.aspx?TrialID=NL7729 .